Study Of The Behavior Of The Suku Anak Dalam Towards Local Wisdom In The Utilization Of Forest Resources In Sarolangun Regency - Saputra, Ardhiyan; Kurniasih, Siti (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
Many indigenous communities still live and depend on forest resources for their livelihoods.Jambi Province is one of the areas that has a nature reserve forest and biosphere reserve called Bukit Duabelas National Park.One example is the Suku Anak Dalam (SAD) in Jambi Province. The SAD community, which still relies on forests for their livelihoods, relies on local wisdom in managing these forest resources. This contrasts sharply with the forest clearing activities carried out by local communities and large plantations that are expansively clearing forests for oil palm plantations. This negatively impacts the SAD community, whose primary livelihood relies on forest resources. Needs that they could have obtained from the forest are lost. Therefore, it is necessary to establish forest areas between production forests and forests for biosphere functions. The behavior of the SAD community towards local wisdom in the utilization of forest resources can have a significant impact on the economy for indigenous communities, especially SAD, and sustainable forest conservation. Using a qualitative descriptive approach, this research plan aims to describe and analyze the behavior of SAD in terms of local wisdom in utilizing forest resources for SAD's livelihood. It is hoped that in the future, SAD's behavior in utilizing forest resources can be wiser and more sustainable.